Operating System Concepts for Reconfigurable Computing: Review and Survey - Marcel Eckert; Dominik Meyer; Jan Haase; Bernd Klauer (International Journal of Reconfigurable Computing)
One of the key future challenges for reconfigurable computing is to enable higher design productivity and a more easy way to use reconfigurable computing systems for users that are unfamiliar with the underlying concepts. One way of doing this is to provide standardization and abstraction, usually supported and enforced by an operating system. This article gives historical review and a summary on ideas and key concepts to include reconfigurable computing aspects in operating systems. The article also presents an overview on published and available operating systems targeting the area of reconfigurable computing. The purpose of this article is to identify and summarize common patterns among those systems that can be seen as de facto standard. Furthermore, open problems, not covered by these already available systems, are identified.